(untitled) (Itinera, 2015)
Enlightenment is not only a movement that happened in history and that would have just left a trace in it, but is also a self-moving process which constitutes our own history. And we respond to this process with an attitude of changing conjugation of times, and an always precarious embodiment of a useful fiction for collective live, what we call democracy. In addition to this, the expressions that surround the exaggerated name Enlightenment (Illuminismo, in Italian) show the intention of the essay: to defend the current appropriateness and the encouragement of a left-wing intellectual attitude.